2022
DOI: 10.3390/ijerph19159467
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally Dependent Change of the Number of Fractures after 50 Years of Age in Poland—Analysis of Combined Health Care and Climate Datasets

Abstract: Aim: The incidence of fractures correlates with many independent and interrelated factors. The aim of the study was to examine trends in fracture incidence and to find possible reasons for changes. Materials and methods: A complete dataset of Polish population aged above 50 from the National Heath Fund—which is a single, state-owned payer for the health service procedures in Poland—covering the years between 2010 and 2015 was analyzed along with climate dataset. Results: The analysis indicated that there was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…We observed a downward trend in hip fracture events irrespective how fractures were ascertained, nding it with a naïve analysis, with o cial Swedish statistics as well as with our more accurate algorithm-based approach. The same downward trend has also been seen in other European settings (31)(32)(33)(34), while trends have plateaued in North America (35). In contrast, hip fracture rates are increasing in Asia (36-39).…”
Section: Discussionsupporting
confidence: 57%
“…We observed a downward trend in hip fracture events irrespective how fractures were ascertained, nding it with a naïve analysis, with o cial Swedish statistics as well as with our more accurate algorithm-based approach. The same downward trend has also been seen in other European settings (31)(32)(33)(34), while trends have plateaued in North America (35). In contrast, hip fracture rates are increasing in Asia (36-39).…”
Section: Discussionsupporting
confidence: 57%
“…[ 27 ] Additionally, Kinga et al found that changes in fracture incidence were related to season (warmer vs colder) and the increase in mean temperature during the observation period. [ 28 ] This could be due to the need for thicker clothing in cold weather, resulting in repeated movements due to the inconvenience of exposing the affected limb during the emergency examination. Furthermore, cold weather may negatively impact patients’ exposure to the external environment at the time of injury and during ambulance transport, potentially leading to hypothermia, which can have detrimental effects on trauma patients’ metabolic and coagulation systems.…”
Section: Discussionmentioning
confidence: 99%
“…and the increase of mean temperature during the observation period [29]. This could be due to the cold weather requiring thicker and additional clothing, resulting in repeated movements due to the inconvenience of exposing the affected limb during the emergency examination.…”
Section: Discussionmentioning
confidence: 99%